2004
DOI: 10.1021/jp047105z
|View full text |Cite
|
Sign up to set email alerts
|

Metallophthalocyanines:  Versatile Electron-Donating Building Blocks for Fullerene Dyads

Abstract: A thorough investigation on the physicochemical properties, including electrochemisty and photophysics, of a new class of donor−acceptor hybrids, namely, phthalocyanine-fullerene dyads, consisting of free base 1a and zinc and copper complexes 1b and 1c, respectively, brings new insights into the stabilization of charge-separated radical ion pairs and the impact of redoxactive transition-metal centers on the photoperformance of macrocyclic phthalocyanines. In these dyads, the role of the phthalocyanines is twof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 41 publications
5
97
1
Order By: Relevance
“…64,66,72,87,101 We determined various ET parameters, including V and , for porphyrin-fullerene systems from the CT absorption and emission for the first time. 64,66,72,87,101 Such CT absorption and emission were also reported for other fullerene-porphyrin-linked [102][103][104][105] and fullerene-phthalocyanine-linked 106 systems. Furthermore, the specific -interaction has been successfully used in dye-sensitized bulk heterojunction solar cells consisting of porphyrin and fullerene (vide infra).…”
Section: Introductionsupporting
confidence: 60%
“…64,66,72,87,101 We determined various ET parameters, including V and , for porphyrin-fullerene systems from the CT absorption and emission for the first time. 64,66,72,87,101 Such CT absorption and emission were also reported for other fullerene-porphyrin-linked [102][103][104][105] and fullerene-phthalocyanine-linked 106 systems. Furthermore, the specific -interaction has been successfully used in dye-sensitized bulk heterojunction solar cells consisting of porphyrin and fullerene (vide infra).…”
Section: Introductionsupporting
confidence: 60%
“…60 Additionally, it has been reported that ZnPc •+ also shows an absorption band at 840 nm. 75,76 This band is known to be broadened by strong π--π interac--tions. 65 Therefore, no observation of the absorption band at 840 nm in Figure 6a together the red shift and broad--ening of the absorption band in Figure 4 suggests strong π--π interactions of ZnPc •+ with graphene.…”
Section: Resultsmentioning
confidence: 99%
“…[6,38] In addition, further tuning of the energy levels of moieties might allow efficient charge generation and extraction along the stacks for use in solar cells. [39][40][41][42] …”
Section: Resultsmentioning
confidence: 99%